Study on the pharmacokinetics, tissue distribution and excretion of laurolitsine from Litsea glutinosa in Sprague-Dawley rats. (1st January 2021) - Tan, Yin-Feng; Wang, Rui-Qi; Wang, Wen-Ting; Wu, Ying; Ma, Ning; Lu, Wei-Ying; Zhang, Yong; Zhang, Xiao-Po
Abstract: Context: Laurolitsine is an aporphine alkaloid and exhibits potent antihyperglycemic and antihyperlipidemic effects in ob/ob mice. Objective: To investigate the pharmacokinetics, tissue distribution and excretion of laurolitsine. Materials and methods: A LC-MS/MS method was established and validated to determine laurolitsine concentrations in the biological matrix of rats (plasma, tissue homogenate, urine and faeces). 10 Sprague-Dawley (SD) rats were used for plasma exposure study: 5 rats were injected with 2.0 mg/kg of laurolitsine via the tail vein, and the other 5 rats were administered laurolitsine (10.0 mg/kg) by gavage. 25 SD rats used for tissue distribution study and 5 SD rats for urine and faeces excretion study: rats administered laurolitsine (10.0 mg/kg) by gavage. After administered, serial blood, tissue, urine and faeces were collected. Analytical quantification was performed by a previous LC-MS/MS method. The pharmacokinetics, bioavailability, tissue distribution and excretion of laurolitsine were described. Results: The pharmacokinetic parameters of oral and intravenous administration with Tmax were 0.47 and 0.083 h, t1/2 were 3.73 and 1.67 h, respectively. Oral bioavailability was as low as 18.17%. Laurolitsine was found at a high concentration in the gastrointestinal tract, liver, lungs and kidneys (26 015.33, 905.12, 442.32 and 214.99 ng/g at 0.5 h, respectively) and low excretion to parent laurolitsine in urine and faeces (0.03 and 1.20% in 36 h, respectively). Conclusions: This study established a simple, rapid and accurate LC-MS/MS method to determine laurolitsine in different rat samples and successful application in a pharmacokinetic study.